FIGURE 27. A, D in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 27. A, D, Achelous ordwayi Stimpson, 1860, male, cl 16.1 mm, cw 28.1 mm (MZUSP 21204). B, E, Achelous tumidulus Stimpson, 1871, ovigerous female, cl 10.5 mm, cw 16.5 mm (MZUSP 41419). C, F, Cronius ruber (Lamarck, 1818), juvenile male, cl 7 mm, cw 10 mm (MZUSP 40173). Note in (B, C) carapace anterolateral teeth unequal, alternating large and small (arrows). Scales: D–F, 0.5 mm. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 52, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155